Capacitive versus Pseudocapacitive Storage in MXene. (8th May 2020) - Ando, Yasunobu; Okubo, Masashi; Yamada, Atsuo; Otani, Minoru
Abstract: MXene electrodes in electrochemical capacitors have a distinctive behavior that is both capacitive and pseudocapacitive depending on the electrolyte. In this work, to better understand their electrochemical mechanism, first‐principles calculations based on the density functional theory combined with the implicit solvation model are used (termed as 3D reference‐interaction‐site model). From the viewpoint of their electronic states, the hydration shell prevents orbital coupling between MXene and the intercalated ions, which leads to the formation of an electric‐double layer and capacitive behavior. However, once the cations are partially dehydrated and adsorbed onto the MXene surface, because of orbital coupling of the cation states with the MXene states, particularly for surface‐termination groups, charge transfer occurs and results in a pseudocapacitive behavior. Abstract : First‐principles calculations combined with the reference‐interaction‐site model reveal that the hydration shell prevents orbital coupling between MXene and the intercalated cations, which maintains charge separation and leads to the capacitive behavior. Once the cations are partially dehydrated and adsorbed onto the MXene surface, charge transfer occurs because of the orbital coupling, resulting in a pseudocapacitive behavior.